Zero Waste Fashion Innovation Inspired by Pacu Jalur Batik Motifs - Della, Miftari; Imelda, Desra (Jurnal Bisnis dan Komunikasi Digital, 2025)
This work aims to create contemporary fashion using zero waste pattern   techniques combined with the Batik Pacu jalur motif as an appreciation for local cultural traditions and to support sustainability in the fashion industry. The theory applied in this work focuses on sustainable design principles that emphasize waste reduction and the optimal use of resources. The methods used include exploring the Pacu jalur culture as an idea source, designing fashion patterns using zero waste techniques, and applying batik motifs inspired by the unique ornaments of Pacu jalur. The resulting work consists of three categories of fashion: ready-to-wear, ready-to-wear deluxe, and haute couture, each embracing the concepts of sustainability and cultural preservation. The presentation of this work is carried out through a fashion show, showcasing a collection that features strong and bold design elements, along with diverse embroidery and stitching techniques to enrich its visual aesthetics. This work functions not only as fashion but also as an artistic statement on the importance of cultural and environmental preservation